Correction of Hypertriglyceridemia as the Way to Reduce Residual Risk in Diseases Caused by Atherosclerosis. Conclusion of the Advisory Board of the Russian Society of Cardiology, the Russian Scientific Medical Society of Therapists, the Eurasian Association of Therapists, the Russian National Atherosclerosis Society, the Russian Association of Endocrinologists, and the National League of Cardiologic Genetics - G. P. Arutyunov; S. A. Boytsov; M. I. Voyevoda; V. S. Gurevich; O. M. Drapkina; V. V. Kukharchuk; A. I. Martynov; I. V. Sergiyenko; M. V. Shestakova; A. S. Aliyeva; N. M. Akhmedzhanov; M. G. Bubnova; et al. (Рациональная фармакотерапия в кардиологии)
Tactics for the management of patients with hypertriglyceridemia (HTG) is provided in the conclusion of the Advisory Board. It is demonstrated that HTG is quite prevalent in patients with excessive body weight and is an important component of residual risk. HTG creates additional conditions for the progression of atherosclerosis, and thus it is recommended to test triglyceride in patients with high, very high and extremely high cardiovascular risk. The indication for the pharmacological treatment to reduce the triglycerides concentration is their level more than 2.3 mmol/l. Statins are drugs of choice aimed to decrease the cardiovascular risk in patients with hypercholesterinemia and HTG. Fenofibrate is used to correct HTG; in case of its intolerance or if the triglyceride target level is not reached, ethyl esters of omega-3 polyunsaturated fatty acid can be used in the dosage of 2-4 g daily. In patients with triglyceride level higher than 5.6 mmol/l, fenofibrate is the main option of treatment.